2021
DOI: 10.1155/2021/5594263
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Electroacupuncture Can Accelerate the Recovery of Gastrointestinal Function in Cancer Patients Undergoing Pancreatectomy or Gastrectomy: A Randomized Controlled Trial

Abstract: The effect of perioperative acupuncture on accelerating gastrointestinal function recovery has been reported in colorectal surgery and distal gastrectomy (Billroth-II). However, the evidence in pancreatectomy and other gastrectomy is still limited. A prospective, randomized controlled trial was conducted between May 2018 and August 2019. Consecutive patients undergoing pancreatectomy or gastrectomy in our hospital were randomly assigned to the electroacupuncture (EA) group and the control group. The patients i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Firstly, the pain of patients was reduced, suggesting that TCM compound therapy for acute pancreatitis may play a therapeutic role from different angles and through different targets. A large number of clinical and basic studies have not only confirmed the therapeutic effect of Chinese herbal formulas on acute pancreatitis but also preliminarily revealed the mechanism of these therapeutic effects [ 28 , 29 ]. Sometimes, fatal acute pancreatitis is caused by a systemic uncontrolled inflammatory response, and the resulting gastrointestinal function damage is one of the main causes of death.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, the pain of patients was reduced, suggesting that TCM compound therapy for acute pancreatitis may play a therapeutic role from different angles and through different targets. A large number of clinical and basic studies have not only confirmed the therapeutic effect of Chinese herbal formulas on acute pancreatitis but also preliminarily revealed the mechanism of these therapeutic effects [ 28 , 29 ]. Sometimes, fatal acute pancreatitis is caused by a systemic uncontrolled inflammatory response, and the resulting gastrointestinal function damage is one of the main causes of death.…”
Section: Discussionmentioning
confidence: 99%
“…ere is no obvious manifestation in the initial stage of the disease, but with the progress of the disease, symptoms such as abdominal pain, hematemesis, melena, and intestinal obstruction may appear and even lead to multiple organ failure, which is life-threatening and has a great impact on the quality of life of patients [2]. At present, surgery, chemotherapy, radiotherapy, and traditional Chinese medicine therapy are common clinical tumor treatments, which have a certain effect on patients with gastrointestinal tumors and can improve the prognosis of patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…Ng and colleagues found that EA reduced the time to first defecation (85.9 hours) as compared with SA (107.5 hours) after laparoscopic surgery in traditional nursing care. In a recently published acupuncture trial, Qiu et al reported that the time to first defecation was 4.2 days and 5.4 days in the EA and SA group, respectively, after pancreatectomy or gastrectomy without the ERAS protocol. The median (IQR) time to first defecation in this trial was 76.4 (67.6-96.8) hours in the EA group and 90.0 (73.6-100.3) hours in the SA group.…”
Section: Discussionmentioning
confidence: 99%